1999
DOI: 10.1016/s0304-3959(99)00107-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial comparing the effects of acupuncture and a newly designed placebo needle in rotator cuff tendinitis

Abstract: Acupuncture has gained increasing attention in the treatment of chronic pain. The lack of a satisfying placebo method has made it impossible to show whether needling is an important part of the method or whether the improvement felt by the patient is due to the therapeutic setting and psychological phenomena. Also, the effectiveness of acupuncture has not been demonstrated sufficiently. We treated 52 sportsmen with rotator cuff tendinitis in a randomised single-blind clinical trial using a new placebo-needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0
16

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(198 citation statements)
references
References 15 publications
4
178
0
16
Order By: Relevance
“…Hay et al 9 reported similar efficacy for subacromial corticosteroid injection and a mix of PT intervention and it is common in clinical practice to combine for example acupuncture with exercises as a treatment for patients with SIS. 5,10 Electro 11 and manual acupuncture 12 alone or combined with home exercises 13 are reported as being probably effective, but the treatment strategies and inclusion criteria of different trials has varied. Overall, the evidence of efficacy seems inconclusive, especially over the long-term.…”
Section: That Includedmentioning
confidence: 99%
“…Hay et al 9 reported similar efficacy for subacromial corticosteroid injection and a mix of PT intervention and it is common in clinical practice to combine for example acupuncture with exercises as a treatment for patients with SIS. 5,10 Electro 11 and manual acupuncture 12 alone or combined with home exercises 13 are reported as being probably effective, but the treatment strategies and inclusion criteria of different trials has varied. Overall, the evidence of efficacy seems inconclusive, especially over the long-term.…”
Section: That Includedmentioning
confidence: 99%
“…Sham / placebo acupuncture administration-Placebo treatment used a validated sham acupuncture needle (Streitberger placebo) [16,17,19,28,31,37,40] and was identical to active manual acupuncture except that the needle was not inserted into the skin and the acupuncturist held and rotated the needle more gently. The sham needles differed from regular needles by possessing blunt and retractable tips.…”
Section: Acupuncture Administrationmentioning
confidence: 99%
“…69 This placebo needle was shown to be perceived by volunteers as similar to the true penetrating acupuncture needle (also held in place via bandaid and ring), 69 and, appropriately, the placebo was significantly less effective in reducing tendinitis pain and discomfort. 70 With or without appropriate blinding and placebo controls, expectations about the credibility (usefulness and efficacy) of unconventional methods such as acupuncture may influence outcome. 71 Such moderating variables may obscure real differences between groups especially in small samples.…”
Section: Research Agendamentioning
confidence: 99%